Integrating LLM-based agents with uncertainty-aware optimization for water-energy-carbon nexus management in irrigation districts - Lei Yu; Zhikai Li; Kai Huang; Fulin Li; Zixiang Lu; Yurui Fan; Yanan Jiang; Chenglong Zhang; Guangtao Fu (Water Research, 2027)

Comparative analysis of GAMLSS modeling approaches for nonstationary runoff dynamics in the Yellow River Basin of China - Ben Niu; Yi Li; Yurui Fan; Lei Gong; Lei Wang; Taishan Wang (Journal of Hydrology, 2026)

Synergistic optimization of water-energy-environment nexus under uncertainty: An interval type-2 fuzzy chance-constrained programming model in a coastal mountainous basin, China - Zhiyi Peng; Lei Jin; Yurui Fan; Li Wang; Jing Liu (Journal of Environmental Management, 2026)

Development of a multi-objective type-2 fuzzy interval stochastic programming model for water allocation in Minnan region integrating agricultural products and greenhouse gas emission under uncertainty - Yi Wei; Lei Jin; HaiYan Fu; Yurui Fan; RuoLin Bai (Environment, Development and Sustainability, 2026)

New strategies for synergistic inhibition of mild steel corrosion by dual-functionalized chitosan: Film formation and Fe2+ adsorption - Minghui Jiang; Xiao Liu; Yurui Xu; Shiyu Li; Xingxin Hu; Xinxin Li; Lei Lu; Ziming Wang; Suping Cui (Journal of Cleaner Production, 2026)

A semi-infinite type-2 fuzzy multi-objective programming model for irrigation water resource management under uncertainties - Enkang Pan; Lei Jin; Yurui Fan; Li Wang (Hydrological Sciences Journal, 2025)

Novel eco-friendly inhibitor for mild steel in simulated concrete pore solution: Experimental and theoretical analysis - Minghui Jiang; Xiao Liu; Xingxin Hu; Shiyu Li; Yurui Xu; Xinxin Li; Lei Lu; Chunlei Xia; Xiangju Liu; Ziming Wang; Suping Cui (Chemical Engineering Journal, 2025)

Improved semi-infinite interval type-2 fuzzy multi-objective programming with integrated multi-criteria decision analysis for sustainable water resource management - Xi Zhang; Lei Jin; Yurui Fan; Li Wang; Jing Liu; Pangpang Gao (Journal of Water Process Engineering, 2025)

Analyzing water resources with sector characteristics in Fujian Province utilizing S2-DR-BIMCCP model integrated with the Gini coefficient - Ruolin Bai; Lei Jin; Yurui Fan; Xi Zhang; Ruoyu Yin; Yi Wei (Journal of Cleaner Production, 2025)

Thermal properties and grey correlation degree analysis of tar-rich coal under cryogenic and pyrolysis condition - Tao Xu; Yurui Lei; Lingyun Chen; Yongping Wu (Fuel, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Projections of future precipitation and air temperature over the Tibetan Plateau based on Coupled Model Intercomparison Project Phase 6 multimodel ensembles - Wenqing Zhang; Liu Liu; Yurui Lun; Lei Cheng; Xiuping Li; Zongxue Xu (International Journal of Climatology, 2022)
In the context of global warming and the release of projection results from the Coupled Model Intercomparison Project Phase 6 (CMIP6), it is important to conduct research on climate change on the Tibetan Plateau (TP) which exhibits unique geographic characteristics and complex climatic conditions. Using 10 general circulation models (GCMs) from CMIP6 corrected for bias by the daily translation (DT) method, we investigated the projected changes in precipitation and air temperature for the mid‐term (2031–2050) and long‐term (2061–2080) of the 21st century on the TP after evaluating the reliability of the bias correction, for four scenarios based on different combinations of shared socioeconomic pathways and representative concentration pathways. The multimodel ensembles (MMEs) indicated that the projected annual precipitation shows an increasing trend for the mid‐term and long‐term periods, with the projected increase for the long‐term primarily concentrated in areas with less precipitation. Meanwhile, the future precipitation changes exhibit a significant elevation dependency. The rate of increase of precipitation firstly fluctuates and then gradually increases along with the elevation increasing from 1,500 to 5,800 m. The valley value of rate mainly appears in two elevation zones (2,200–2,600 m and 3,400–3,800 m). The projected temporal changes in annual air temperatures reveal obvious warming over the TP. The projected warming is overall more pronounced with increase in elevation; however, it reaches a peak at approximately 5,000–5,200 m and then slows down slightly, indicating that warming is not dependent on elevation in the higher elevation zones. The present results have important implications for investigating the impacts of climate change on the water cycle in alpine regions.

Assessment of GCMs simulation performance for precipitation and temperature from CMIP5 to CMIP6 over the Tibetan Plateau - Yurui Lun; Liu Liu; Lei Cheng; Xiuping Li; Hao Li; Zongxue Xu (International Journal of Climatology, 2021)
General circulation models (GCMs) are indispensable for climate change adaptive study over the Tibetan Plateau (TP), which is the potential trigger and amplifier in global climate fluctuations. With the release of Coupled Model Intercomparison Project Phase 6 (CMIP6), 24 GCMs from CMIP5 and CMIP6 were comparatively evaluated for precipitation and air temperature simulations based on the China Meteorological Forcing Dataset (CMFD). Rank score results showed that CMIP6 models generally performed better than CMIP5 for precipitation and surface air temperature over the TP. According to multimodel ensembles (MMEs) of the optimal GCMs for each climate variable, the overestimation of precipitation was both present in CMIP5 and CMIP6, but the results of CMIP6 MMEs were relatively lower in the mid‐west and northern edge of the TP. Furthermore, CMIP6 offered a better performance of precipitation in summer and autumn. For temperature, CMIP6 MMEs were able to reduce the relatively large cold bias that appeared in CMIP5 MMEs in northwest areas to about 1°C and had a smaller bias in spring and winter. Moreover, the investigation into the simulation effects of precipitation at different elevation zones demonstrated that the improved ability of CMIP6 MMEs to reduce bias was mainly concentrated in the elevation zones of 2,000–3,000 m and over 5,000 m, where the precipitation bias was more than 200%. Additionally, CMIP6 MMEs of temperature were able to reduce the bias to less than 2°C in each elevation zone, with the minimum bias of −0.22°C distributed in the region with altitudes from 3,000 to 4,000 m, while the biases of CMIP5 MMEs in the region of 4,000–5,000 m and over 5,000 m were smaller than those of CMIP6 MMEs. Findings obtained in this study could provide a scientific reference for related climate change research over the TP. GCMs of CMIP6 perform better than those of CMIP5 for precipitation and temperature over the TP. Multimodel ensembles (MMEs) of CMIP6 effectively reduce the overestimation of precipitation from CMIP5 MMEs by 40 mm at the annual scale. Improved ability of CMIP6 MMEs shows a significant elevation dependency, especially in elevation zones of 2,000–3,000 m and over 5,000 m for precipitation.

A Hybrid Dynamic Dual Interval Programming for Irrigation Water Allocation under Uncertainty - Lei Jin; Guohe Huang; Yurui Fan; Xianghui Nie; Guanhui Cheng (Water Resources Management, 2012)